Identification and sensitivity testing of whip smut pathogen on sugarcane to fungicides and plant extracts - Efri, Efri; Nisa, Ummu Khairun; Pramono, Sudi; Maryono, Tri; Saefudin, Saefudin; Pranata, Heru (Universitas Lampung, 2025)
Whip smut symptoms have emerged in sugarcane plantations in Central Lampung Regency, Lampung Province. However, the identity of the pathogen and its sensitivity to various fungicidal active ingredients remain unclear. This study aims to identify the whip smut pathogen in sugarcane plantations in Central Lampung Regency and evaluate its sensitivity to different fungicidal active ingredients.The research involved morphological and molecular identification of the pathogen, along with sensitivity testing against fungicides containing carbendazim, prochloraz, and mancozeb, as well as plant-based fungicides derived from puyangan (Zingiber zerumbet) and jamuan (Curcuma zedoaria) extracts. Morphological analysis revealed that the whip smut pathogen has septate hyphae, cylindrical sporidia measuring 7.45–18.31 µm in length and 1.63–3.89 µm in width, and round, yellowish-brown teliospores with an average size of 6.39 × 6.66 µm. Molecular identification confirmed that the LA UKN isolate from Central Lampung Regency belongs to Sporisorium scitamineum, with a bootstrap value of 93%. Sensitivity testing indicated that the pathogen is highly susceptible to carbendazim and prochloraz but less sensitive to mancozeb, puyangan extract, and jamuan extract.